Virucidal properties of DEO-SEPT upon Vaccinia virus through quantitative suspension test M. Danes, Carmen Moisoiu, - Danes, M.,; Carmen Moisoiu; Mihaela Scripcariu,; Rodica Moise,; Doina Surugiu,; Doina Danes (Medicamentul Veterinar)
Antiseptics and disinfectants are used extensively in hospital sand other health care settings for a variety of topical and hard-surface applications. In particular, they are an essential part of infection control practices and aid in the prevention of nosocomial infection. The virucidal efect of the DEO-SEPT product was demonstrated on the vaccinia virus strain Elstree (Essen University Origin) which has been passaged 10 times in GMK-AH1 (green monkey kidney cell line), three times in HeLa cells and five time in Vero cells (monkey kidney cell line). Evaluation of the effectiveness was done in a quantitative suspension test according with DVV (German Association of the Control of Virus Disease) and RKI (Robert Koch Institute) guideline at the 0.5%, 1% and 2% concentration. The contact time was 5, 15, 30 and 60 minutes into the present of the control product based on formaldehyde. The results showed the 99.9% inactivation of the initial virus titer (means >4log10 of the initial titer) at 2% after 5 minutes.